Increasing Nagari Syariah Bank Customer Satisfaction Through Easy Transactions - Febriyanti, Siska (AL-FALAH : Journal of Islamic Economics, 2024)
Purpose: The aim of this research is to determine the relationship between facility conditions and customer convenience in transactions with customer satisfaction at Bank Nagari Syariah. This is based on the fact that although the facilities and infrastructure at the Bank are still inadequate, the number of assets and pooled funds from the public at Bank Nagari Syariah continues to increase. Design/Method/Approach : The method used in this research is a qualitative method, with data collection techniques through documentation. Findings: The method used in this research is a qualitative method, with data collection techniques through documentation. Originality/Values: This study shows that even though the facilities of several Bank Nagari Sub Branches are not very adequate However, customer satisfaction is still high with Bank Nagari Syariah. This could be because customers are given various conveniences in carrying out transactions, namely through digital e-banking applications, so that the condition of office facilities does not really affect customer satisfaction.